2020
DOI: 10.3390/pharmaceutics12060497
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotection, Genoprotection, and Dermal Exposure Assessment of Chitosan-Based Agronanofungicides

Abstract: Health risks which result from exposure to pesticides have sparked awareness among researchers, triggering the idea of developing nanoencapsulation pesticides with the aim to enhance cytoprotection as well as genoprotection of the pesticides. In addition, nanocapsules of pesticides have slow release capability, high bioavailability, and site-specific delivery, which has attracted great interest from researchers. Hence, the objective of this work is to synthesize a nanoformulation of a fungicide of different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…), with four times lower halfmaximal effective concentration (EC 50 ) and disease reduction up to 75% [82]. Furthermore, chitosan-based agronanofungicides phytotoxicity, cytotoxicity, and genotoxicity studies revealed the superiority of the chitosan nanoparticles, in which they act as a defensive wall to shield the fungicide's toxic effect on oil palm seedlings, cells, and DNA [83,84]. Long half-lives (t 1/2 ) of fungicide in stem tissue and leaf tissue were also discovered at 383 and 515 days, respectively, indicating high uptake and retention time, indicating the ideal desired properties for chitosan-based agronanofungicides for improved management of oil palm basal stem rot disease [85].…”
Section: Nanotechnology Advancements In Agriculturementioning
confidence: 99%
“…), with four times lower halfmaximal effective concentration (EC 50 ) and disease reduction up to 75% [82]. Furthermore, chitosan-based agronanofungicides phytotoxicity, cytotoxicity, and genotoxicity studies revealed the superiority of the chitosan nanoparticles, in which they act as a defensive wall to shield the fungicide's toxic effect on oil palm seedlings, cells, and DNA [83,84]. Long half-lives (t 1/2 ) of fungicide in stem tissue and leaf tissue were also discovered at 383 and 515 days, respectively, indicating high uptake and retention time, indicating the ideal desired properties for chitosan-based agronanofungicides for improved management of oil palm basal stem rot disease [85].…”
Section: Nanotechnology Advancements In Agriculturementioning
confidence: 99%
“…Changes within genetic materials can occur directly or indirectly, thereby affecting somatic or germ cells that may be passed on to the next generation (Basu, 2018). Damages to DNA caused by free radicals, ionising radiations, alkylating agents, and nanoparticles could be DNA strand breaks, DNA adducts, or other types of DNA-base modifications which are recognised and fixed by various DNA repair mechanisms (Chatterjee and Walker, 2017;Maluin et al, 2020;Siew et al, 2020).…”
Section: Introductionmentioning
confidence: 99%